Physical and Mechanical Properties of Compressed Earth Brick (CEB) with Palm Oil Fuel Ash (POFA) as Cement Replacement - Zainal, Lydiea Aura; Burhanudin, Mohd Khairy (Recent Trends in Civil Engineering and Built Environment, 2024)
Malaysia is the largest palm oil producer where palm oil fuel ash (POFA) is a solid waste that were difficult to remove but the waste can be used to solve solid waste problem. POFA is a pozzolanic material that can replace Ordinary Portland Cement (OPC) in order to produce high strength and low-cost bricks. Replacement of POFA can be considered as environmentally friendly. Palm oil fuel ash (POFA) was used as a component in compressed earth brick (CEB) in this study to replace cement. The purpose of this study was to determine the density, water absorption and compression strength of CEB. The dimension of CEB produced was 250 mm x 125 mm x 100 mm and the mix ratio is 1:4:4 for cement, sand and soil respectively. 0%, 5%, 10%, 15%, and 20% from cement content are the five types of percentages used. A total of 60 pieces of CEB was produced. CEB was given a 7-day and 28-day curing process before the test. The test conducted were density test, water absorption and compressive strength test. The results showed that CEB specimens with 10% POFA had the maximum density and compressive strength after 28 days, with values of 2099.4 kg/m3 and 3.4559 N/mm2, respectively. The CEB specimen with 0% POFA for 28 days had the lowest rate of water absorption which is 9.5% and it in compliance with MS 76: 1972 that allowable 15% of water absorption for an earth brick. Therefore, as a result of findings, solid waste such as POFA was identified to be suitable materials in part of construction. However, more research is needed in term of chemical composition and other aspects to improve the understanding before it can be used in brick manufacture.